2022
DOI: 10.3233/jad-210681
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy in Early Onset Alzheimer’s Disease

Abstract: Background: Epilepsy seems to be an important comorbidity in patients with early onset Alzheimer’s disease (EOAD). Currently, seizures are still underestimated in this population. However, seizures may interact with AD evolution with possible acceleration of cognitive decline and early institutionalization. Objective: To better define the epileptic disorders observed in patients with EOAD. Methods: All patients diagnosed as EOAD in our hospital between 2013 and 2019 and with positive CSF biomarkers for AD were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 55 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Patients with AD can also have generalized tonic–clonic seizures, as well. In 10 early onset Alzheimer’s disease (EOAD) patients with epilepsy, seizure types included generalized onset tonic-clonic seizures (25%), temporal lobe seizures (25%), myoclonus (25%), focal onset extra-temporal seizures (8%), and other types (17%) ( 37 ).…”
Section: Seizure Semiology and Clinical Course In Alzheimer’s Diseasementioning
confidence: 99%
“…Patients with AD can also have generalized tonic–clonic seizures, as well. In 10 early onset Alzheimer’s disease (EOAD) patients with epilepsy, seizure types included generalized onset tonic-clonic seizures (25%), temporal lobe seizures (25%), myoclonus (25%), focal onset extra-temporal seizures (8%), and other types (17%) ( 37 ).…”
Section: Seizure Semiology and Clinical Course In Alzheimer’s Diseasementioning
confidence: 99%
“…Younger AD patients were found to be more likely to have unprovoked seizures, with a 87-fold increase in the age group of 50–59 years as compared to the age-matched general population [ 18 ]. Epilepsy has been stated as a frequent comorbidity in early-onset AD [ 19 ]. A recent study by Horvath et al confirmed that AD patients with epileptic discharges on EEG and/or epileptic seizures had a dementia onset at a younger age.…”
Section: Introductionmentioning
confidence: 99%